Origins of strengthening and failure in twinned Au nanowires: Insights from in−situ experiments and atomistic simulations - Xie, Zhuocheng; Shin, Jungho; Renner, Jakob; Prakash, Aruna; Gianola, Daniel S.; Bitzek, Erik (Acta Materialia, 2020)
The deformation behavior of ⟨110⟩-oriented twinned Au nanowires (NWs) with multiple longitudinal coherent twin boundaries (CTBs) under tension is studied using in−situ experiments and molecular dynamics (MD) simulations. The twinned NWs show higher yield strength than the single-crystalline NWs with similar diameter. Postmortem observations using electron microscopy and MD simulations show that the presence of CTBs transitions the governing mechanism from twinning-mediated deformation in single-crystalline NWs to strongly localized deformation. MD simulations reveal that the intersection of deposited partial dislocations at the CTB with the free surfaces plays an important role in the transmission of the dislocation, leading to the formation of full dislocations instead of partial dislocations and twinning in the case of single-crystalline NWs. The repeated activation of full dislocation slip leading to localized deformation is furthermore dependent on the relative orientation of surface facets to the activated Burgers vectors. The results of this work enhance the understanding of deformation mechanisms of twinned nano-objects and suggest design strategies for mechanical systems at the nanoscale.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Coherent twin boundary; In−situ tension test; Molecular dynamics; Nanowire; Plasticity